Teach to develop talent: how to motivate and engage tomorrow's innovators today - Paynter, Jeanne L. (Thousand Oaks, CA : Corwin, 2021)
'This book presents a comprehensive, practical, evidence-based approach to transform teaching and learning to focus on the long-term aim of educating our future creative problem-solvers who will identify, develop, and apply their diverse gifts and talents in meaningful ways. Current research that shows even our best schools may not be preparing students for the challenges of the current global economy. The Global Education Reform Movement, with its emphases on standardization, accountability, and testing, has left many of our students disengaged, unmotivated, and underachieving. The most serious crises occur among poor and minority students with potential for high achievement but little opportunity to develop it. Schools need a comprehensive approach for motivating, engaging, and educating innovators across diverse student populations. This book presents such an approach through a new model called Talent-Targeted Teaching and Learning, a brain-based model for talent development which fosters students' content expertise, metacognition, and creative problem-solving. This model demonstrates how students can achieve the required curriculum content standards while they work toward long-range aims for talent development. Educators learn hands-on techniques to target, teach, and assess the cognitive and psychosocial aptitudes of students, such as creativity, insight, persistence, and logical reasoning. Talent-Targeted Teaching and Learning applies the psychology of motivation, engagement, and achievement to practical methods that educators can use to develop a curriculum focused on long-term aims for talent development'--
Includes bibliographical references and index.
Keywords: Gifted children -- Education; Problem solving -- Study and teaching; Motivation in education